A Conceptual Model of Electronic Word of Mouth Communication through Social Network Sites: The Moderating Effect of Personality Traits - Majali, Tha'er A; Bohari, Abdul Manaf (International Review of Management and Marketing, 2016)
Social network sites have become an essential part in today's world due to its ubiquities, interactivity and its applicability in different contexts. Information exchange is one of the most important practices on Social Network Sites (SNSs). Individuals tend to generate electronic word of mouth (e-WOM) in their social network to tell others about their consumption experiences with specific product or service. Only in recent time, e-WOM communication has serious academic and managerial attention. However, most of prior researches have examined e-WOM effectiveness, intensity and receiver adoption determinants, few studies have investigated the factors that enhance individual's intention to share their related-product information. With regard to the different nature of SNSs this paper aims to detect what drive individuals to share their consumption experience or product related-information in such online environment. The paper proposes that social relational factors; trust, reciprocity, and sense of community are positively associated with user's intention to share their related-product information in form of e-WOM through SNSs. The study also proposes that individuals' personality traits moderate the relationship between social relational factors and intention to share e-WOM through SNSs. Keywords: E-WOM Engagement, Social Relational Factors, Personality Traits JEL Classifications: O310, O330, M310